Impact of weight loss achieved through gastric sleeve surgery with circulating level of ghrelin hormone in obese Iraqi subjects. - Razak Abdl Ghani, Zainab A.; Mukhtar, Ramiz S.; Fadhel, Muayad A.; Turki, Kisma M. (Journal of the Faculty of Medicine Baghdad, 2015)
Back ground: The epidemic of obesity is a major health problem in the developed world with a great influence on morbidity and mortality.The aim of study: to evaluate serum ghrelin levels achieved through LSG and on insulin resistance and the serial changes of insulin concentration in obese patients following gastric sleeve.Patients and methods: twenty four patients underwent LSG with 25 controls were selected. Body mass index (BMI), waist circumference (WC), lipid profile, fasting blood sugar (FBS), glycated hemoglobin (HbA1c), fasting insulin, QUICKI and ghrelin hormone concentrations were measured for controls and patients prior LSG, then one month and three months post-surgery.Results: A significant decline was noticed in BMI, WC, TC, TG, LDL-cholesterol, fasting insulin, and ghrelin, with significant increase in QUICKI in patients undergone LSG with significant differences in all studied parameters between patients and controls. A negative correlation was noticed between ghrelin and BMI in patients before sleeve gastrectomy.Conclusion: Ghrelin is a hormone closely linked with obesity taking into account the marked loss in appetite in the period after laparoscopic sleeve gastrectomy.